The concept of wilayah (responsibility) according to Ibn Taymiyyah - Mohammed Muneer’deen Olodo, Al-Shafi’i; Mohd Safri, Ali; Engku Ibrahim, Engku Wok Zin; Mohd Hasrul, Shuhari; Razali, Musa; Habibat, Oladosu-Uthman; Wan Mohd Hazizi, Wan Mohd Shuimy; Auwal, Abdullah (2020)
The sudden and insisting emergence of various people claiming wilayah (being given responsibility by Allah SWT) nowadays is a call that alarms. It calls for serious attentions from those who are in authority. There are two kinds of wilayah according to Ibn Taymiyyah; that of Allah SWT and that of al-Shaytan. There are those chosen by Allah and there are those who have preferred their adherence to Shaytan, we must differentiate between these and those, as clarified by Allah swt and His Messenger s.a.w. The chosen ones of Allah swt are the believers and the followers of Shaytan are not, and it has been difficult for people in this contemporary age to differentiate between the two; they know not the way to distinguish between their qualities and think that anyone on whose hand strange things occur could be regarded as the one chosen by Allah swt. This extends to not only the hotels and tourism pacts but anyone who is saddled with responsibility. This paper is based on clarifying the whims associated to al-Wilayah (guardianship) from the perception of Ibn Taymiyyah and his writings. The paper employs library, inductive and analytical approach to collect and analyze the required data, which are collected from books and scholarly articles of both ancient and contemporary scholars. The paper basically relies on the Qur’anic verses, prophetic traditions, the statements of companions and their successors, as well as scholars who thread their path. Thus, the central focus of the article is to clarify the concept of being saddled with wilayah from the point of view of the Ahl al-Sunnah wa al-Jama’ah (ASWAJA) as established in the Qur'an and Sunnah, through Ibn Taymiyah and his writings.